The Complete Mitochondrial Genome of Pennella sp. Parasitizing Thunnus albacares - Liu, Hongyan; Fu, Zhengyi; Zhou, Shengjie; Hu, Jing; Yang, Rui; Yu, Gang; Ma, Zhenhua (Frontiers in Cellular and Infection Microbiology, 2022)
In the study, the parasite from the yellowfin tuna (Thunnus albacares) was separated, and morphological observation and molecular identification were carried out. Our results showed that the parasite was similar to Pennella sp. Its cephalothorax was covered by spherical to spherical non-branched nipples of almost the same size, which were very similar in shape and arrangement. A pair of slightly larger, the unbranched antenna was present on the outer margin of the small papillae-covered area. The gene sequence of COX1 with a length of 1,558 bp in the mitochondria of the parasite was 100% similar to Pennella sp. (MZ934363). The mitochondrial genome had a total length of 14,620 bp. It consisted of 36 genes (12 protein-coding, 22 transfer RNAs and 2 ribosomal RNAs) and a dummy control region, but the mitochondrial genome had no ATP8 gene. Morphological observation showed that Pennella sp. was dark red, with a convex cephalothorax, with a total length of 8.42 cm, parasitic on the dorsal side of yellowfin tuna. Pennella sp. included the cephalothorax, neck, trunk, abdomen and egg belt. This study was the first report on the mitochondrial genome of Pennella sp. The results provide basic data for further identifying the parasites of Pennella genus.